2015
DOI: 10.1039/c4sc03046j
|View full text |Cite
|
Sign up to set email alerts
|

Large, heterometallic coordination cages based on ditopic metallo-ligands with 3-pyridyl donor groups

Abstract: The two-step synthesis of large, heterometallic coordination cages based on ditopic 3-pyridyl ligands is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 57 publications
1
64
0
1
Order By: Relevance
“…Like 4-pyridyl linkers, 3-pyridyl substituents can act as metal-bridging ligandsb ut give rise to different supramolecular architectures as ad irect result of the different disposition of the N-donor atoms within the ligand nodes.T he comparativea bsence of ligandsb ased on 3-pyridyl donor sets has been ascribed to inherent synthetic difficulties [1] and also to their conformational flexibility,w hich entropically favours formationo fs mall aggregates. [2] Severin and co-workersh ave overcome this tendency by incorporatinga dditional steric groups into bis(3-pyridyl) Fe clathrochelate ligandst op roduce Pd 6 L 12 12 + cages, [2] and have found that tuningt he sterics alters the size of the cage. [3] This metalloligand strategy for the construction of heterometallic supramolecular architectures has been successfully enacted for av ariety of mixed transition metals ystems, for example, Fe/Pd, [2,[4][5][6] Fe/Ru, [7] Fe/Co, [8,9] Co/ Mn [5] and Ru/Pd.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like 4-pyridyl linkers, 3-pyridyl substituents can act as metal-bridging ligandsb ut give rise to different supramolecular architectures as ad irect result of the different disposition of the N-donor atoms within the ligand nodes.T he comparativea bsence of ligandsb ased on 3-pyridyl donor sets has been ascribed to inherent synthetic difficulties [1] and also to their conformational flexibility,w hich entropically favours formationo fs mall aggregates. [2] Severin and co-workersh ave overcome this tendency by incorporatinga dditional steric groups into bis(3-pyridyl) Fe clathrochelate ligandst op roduce Pd 6 L 12 12 + cages, [2] and have found that tuningt he sterics alters the size of the cage. [3] This metalloligand strategy for the construction of heterometallic supramolecular architectures has been successfully enacted for av ariety of mixed transition metals ystems, for example, Fe/Pd, [2,[4][5][6] Fe/Ru, [7] Fe/Co, [8,9] Co/ Mn [5] and Ru/Pd.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Severin and co-workersh ave overcome this tendency by incorporatinga dditional steric groups into bis(3-pyridyl) Fe clathrochelate ligandst op roduce Pd 6 L 12 12 + cages, [2] and have found that tuningt he sterics alters the size of the cage. [3] This metalloligand strategy for the construction of heterometallic supramolecular architectures has been successfully enacted for av ariety of mixed transition metals ystems, for example, Fe/Pd, [2,[4][5][6] Fe/Ru, [7] Fe/Co, [8,9] Co/ Mn [5] and Ru/Pd. [10,11] However,t he use of main group metalloligands to createmixed main group/transitionmetal heterometallic systems is rare.…”
Section: Introductionmentioning
confidence: 99%
“…a high degree of structural flexibility paired with a limited resolution of the experimental data. DSR has already been successfully employed in that context Wise et al, 2015;Wood et al, 2015).…”
Section: </Name>mentioning
confidence: 98%
“…In den letzten Jahren entstand der Trend, die Komplexität der modular passgenauen Bausteine zu erhöhen und so Form und Topologie des Käfigs sowie dessen Funktion zu verändern 3. Orthogonale Donoren in multifunktionellen Liganden erlauben es, gezielt heteronukleare Strukturen zu synthetisieren, meist auf Basis des HSAB‐Prinzips (harte und weiche Säuren und Basen; Abbildung 2) 4,5…”
Section: Variationsreichunclassified